A novel antibiotic combination of linezolid and polymyxin B octapeptide PBOP against clinical Pseudomonas aeruginosa strains - Ting Huang; Mao Zeng; Huiyao Fu; Kelei Zhao; Tao Song; Yidong Guo; Jingyu Zhou; Longfei Zhai; Chaolan Liu; Balakrishnan Prithiviraj; Xinrong Wang; Yiwen Chu (BMC, 2022)
Abstract Background Antibiotic-resistant Gram-negative bacteria are becoming a major public health threat such as the important opportunistic pathogen Pseudomonas aeruginosa (P. aeruginosa). The present study investigated enhancement of the linezolid spectrum, which is normally used to treat Gram-positive bacteria, at inhibiting P. aeruginosa growth. Methods The checkerboard test or time-kill assay were carried out to determine the antibacterial effects of linezolid in cooperation with polymyxin B octapeptide PBOP (LP) against P. aeruginosa based on in vitro model. The protective effect of LP against P. aeruginosa infection was assessed based on a Caenorhabditis elegans (C. elegans) model. Results The synergistic activity and antibacterial effects were significantly increased against P. aeruginosa by LP treatment, while linezolid and PBOP as monotherapies exhibited no remarkably bactericidal activity against the clinical strains. Additionally, LP treatment modified biofilm production, morphology, swimming motility of P. aeruginosa, and protected C. elegans from P. aeruginosa infection. Conclusions This research demonstrates that LP combination has significant synergistic activity against P. aeruginosa, and PBOP is potential to be an activity enhancer. Notably, this strategy improved the antibacterial activity spectrum of linezolid and other anti-Gram-positive agents and represents an effective choice to surmount the antibiotic resistance of bacteria in the long term.